Global research collaboration in a pandemic-challenges and opportunities: the COVID-19 Global Rheumatology Alliance - Robinson, Philip C. (Curr Opin Rheumatol, 2021)
PURPOSE OF REVIEW: This review discusses the coronavirus disease-2019 (COVID-19) Global Rheumatology Alliance (GRA), the reason for its formation, the challenges with running the registry, and future opportunities for global collaborative research in rheumatology. RECENT FINDINGS: The GRA has been successful in collecting and publishing a large volume of case data on patients with rheumatic disease with COVID-19. In addition, the GRA has published reviews, opinion pieces, and patient-directed summaries of research to further assist in disseminating timely and accurate information about COVID-19 in rheumatic diseases. There have been numerous challenges in the journey but they have been addressed through a collaborative problem-solving approach. SUMMARY: The initial objectives of the GRA to describe the outcomes in patients with rheumatic disease who developed COVID-19 have been achieved. There has been extensive use of the data in the clinic and also to try and understand the mechanisms of disease and opportunities for drug repurposing. There remain numerous important areas for research which the GRA will continue to pursue as the pandemic evolves.